2004
DOI: 10.1038/sj.bjc.6601783
|View full text |Cite
|
Sign up to set email alerts
|

A novel biweekly multidrug regimen of gemcitabine, oxaliplatin, 5-fluorouracil (5-FU), and folinic acid (FA) in pretreated patients with advanced colorectal carcinoma

Abstract: Previous results suggest that GEM affects 5-fluorouracil (5-FU) metabolism and pharmacokinetics in cancer patients, while combined with oxaliplatin, levo-folinic acid, and 5-FU (GOLF regimen), at doses achievable in cancer patients, determines high cytotoxic and proapoptotic antitumour activity in colon cancer cells in vitro. On these bases we designed a phase I -II clinical trial testing the GOLF regimen in patients with metastatic colorectal carcinoma, who had received at least a prior line of chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…These findings have been supported by the results of three recent clinical trials showing the powerful antitumor activity of the GOLF regimen in patients with metastatic colorectal and gastric cancer (Ref. 7 and manuscript submitted for publication).…”
Section: Effects Of Golf Regimen On Colon Cancer Cells In Vitromentioning
confidence: 54%
See 1 more Smart Citation
“…These findings have been supported by the results of three recent clinical trials showing the powerful antitumor activity of the GOLF regimen in patients with metastatic colorectal and gastric cancer (Ref. 7 and manuscript submitted for publication).…”
Section: Effects Of Golf Regimen On Colon Cancer Cells In Vitromentioning
confidence: 54%
“…1). The GOLF combination has also been tested in clinical trials in advanced colon cancer patients in whom it has been shown to have a good safety profile and highly significant antitumor activity (7).…”
mentioning
confidence: 99%
“…On the basis of preclinical findings (5), we designed a novel therapeutic regimen that includes a sequential combination of 5-FU-based polychemotherapy (gemcitabine, oxaliplatin, levofolinic acid, and 5-FU; ref. 6), followed by the immune-adjuvant cytokine recombinant granulocyte macrophage colony-stimulating factor (rGM-CSF), and ultra low-dose metronomic human recombinant interleukin-2 (aldesleukine rIL-2). rGM-CSF was included in the aim to activate peripheral dendritic cells (DC) and rIL-2 to endure an antitumor antigen-specific T-cell-mediated immune response.…”
Section: Introductionmentioning
confidence: 99%
“…6 The GOLF combination has also been used in the treatment of advanced colon and gastric cancer patients and shown a good safety profile and highly significant anti-tumor activity. [15][16][17] The favorable anti-tumor activity of GOLF regimen could be explained by changes of the pharmacokinetics and pharmacodinamics of both 5-FU and OXA induced by GEM (refs. 8, 9 and unpublished results).…”
Section: Introductionmentioning
confidence: 99%